Blockchain in education - V. Grigoriev (Informaciâ i Innovacii)
The article reveals the role and importance of blockchain technology in education, provides a mechanism for solving educational problems with blockchain, describes specific educational projects based on blockchain technology: registry of diplomas, information and educational platforms, online courses, schools, higher education institutions and their associations, using blockchain technology for training, blockchain-based education financing models; blockchain specialists are trained.